NORA moving forward: Developing an oyster restoration network in Europe to support the Berlin Oyster Recommendation. Issue 11 (12th November 2020) - Pogoda, Bernadette; Boudry, Pierre; Bromley, Cass; Cameron, Tom C.; Colsoul, Bérenger; Donnan, David; Hancock, Boze; Hugh‐Jones, Tristan; Preston, Joanne; Sanderson, William G.; Sas, Hein; Brown, Janet; et al.
Abstract: The Native Oyster Restoration Alliance (NORA) supports the protection and ecological restoration of the native European oyster, Ostrea edulis, and its habitat across its current and historical biogeographical range. NORA works to overcome barriers to the conservation, restoration, and recovery of the European oyster by providing a platform for the NORA community to collaborate and participate in knowledge exchange. NORA seeks to support responsible restoration practice, in compliance with biosecurity and sustainability. Against this background, the NORA community formulated a series of specific recommendations, the Berlin Oyster Recommendation, to support native oyster restoration by developing and applying best practice with the aim to recover healthy and resilient marine ecosystems. In combination with the Standards for Ecological Restoration (SER) and the Restoration Guidelines for Shellfish Reefs, the Berlin Oyster Recommendation is a relevant tool for successful and sustainable oyster restoration in Europe. The establishment of NORA working groups will support the implementation and further development of the six corresponding recommendations. Current NORA working groups cover site selection, biosecurity, production, and monitoring. The site selection working group will address the identification of suitable sites for oyster restoration to support policy relevant decision making and the conservation, reinforcement, or reintroduction of native oysters. The biosecurity working group will develop biosecurity guidelines for native oyster restoration in Europe. The production working group will assess the potential of standards for seed oyster production and supply in order to enhance production appropriate for restoration purposes. In close collaboration with the Native Oyster Network – UK & Ireland (NON), the monitoring working group will produce a monitoring guidelines handbook to provide metrics and methods that will be suitable across the range of O. edulis projects in Europe for the documentation of restoration success and ecosystem recovery. The Berlin Oyster Recommendation was examined and interpreted by NORA experts in the context of the further development of joint guidelines for the practice of successful and sustainable native oyster restoration.